Determinants of stunting in children aged between 6–23 months in Musanze region, Rwanda - Umwali, Nadine; Kunyanga, Catherine Nkirote; Kaindi, Dasel Wambua Mulwa (Frontiers in Nutrition, 2022)
Under-nutrition causes approximately half of all deaths in young children every year globally which is exacerbated by the multiple malnutrition burden. Infant and young child feeding practices pose immediate effects on the nutrition status of under two years aged children and greatly influence the survival of a child. This study aimed at determining the implication of the infant and young child feeding practices in evaluating stunting in young children among other stunting risk factors. Analytical cross-section study was carried out in Musanze, a district of Rwanda and involved 241 mothers having children aged between 6 and 23 months. Data was collected using a validated semi-structured questionnaire with observations and check list guides. Chi-square test and logistic regressions were used to determine the associations and risk factors of various variables. The results show that minimum meal frequency (MMF) was attained at 83% rate, minimum dietary diversity (MDD) at 57%, minimum acceptable diet (MAD) at 53% with consumption of iron rich foods at 29%. Stunting prevalence was 28%. The MAD had a significant (p=0.021) association with height-for-age Z-score of a child and was found to be the stunting’s predictor. The child’s sex, consumption of animal sourced foods, child underweight status and income type were revealed as other stunting risk factors. A holistic approach that promotes infant and young child feeding practices and complementary feeding in particular can contribute to the alleviation of the stunting burden in Rwanda. Further, other associated factors that influence child nutrition status should be taken into consideration by the policy decision makers and development partners when developing food and nutrition sensitive programs and interventions.